2013
DOI: 10.1002/pssr.201307165
|View full text |Cite
|
Sign up to set email alerts
|

Light‐induced degradation in indium‐doped silicon

Abstract: Light‐induced degradation of charge carrier lifetime was observed in indium‐doped silicon. After defect formation, an annealing step at 200 °C for 10 min deactivates the defect and the initial charge carrier lifetime is fully recovered. The observed time range of the defect kinetics is similar to the well known defect kinetics of the light‐induced degradation in boron‐doped samples. Differences between defect formation in boron‐ and indium‐doped silicon are detected and discussed. A new model based on an accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 25 publications
(36 reference statements)
2
39
0
Order By: Relevance
“…There are apparent conflicts in the literature regarding whether the properties of indium doped silicon change upon illumination, with some reporting stability and others a substantial degradation. Möller and Lauer found substantial lifetime degradation in indium doped samples, with degradation occurring much more slowly than in our samples . A recent study by Cho et al found that passivated emitter rear cells (PERC) made from indium doped silicon do not degrade under illumination, and Binns et al also concluded that only negligible lifetime degradation occurs in indium doped silicon upon light soaking .…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…There are apparent conflicts in the literature regarding whether the properties of indium doped silicon change upon illumination, with some reporting stability and others a substantial degradation. Möller and Lauer found substantial lifetime degradation in indium doped samples, with degradation occurring much more slowly than in our samples . A recent study by Cho et al found that passivated emitter rear cells (PERC) made from indium doped silicon do not degrade under illumination, and Binns et al also concluded that only negligible lifetime degradation occurs in indium doped silicon upon light soaking .…”
Section: Discussionsupporting
confidence: 49%
“…In indium doped silicon, substantial lifetime degradation occurs in <1 second, with the lifetime then decaying to a steady state in a few minutes. As suggested by Möller and Lauer, we find that a 200°C anneal reverses the LID, and, as shown in Figure (a), the lifetime then again degrades under illumination at approximately the same rate as on previous degradation cycles.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The drawback is that these have even smaller segregation coefficients than gallium of 2 × 10 −3 and 4 × 10 −4 , respectively [55,56]. Furthermore, aluminium is susceptible to the formation of recombination active defects with O i [57] and indium doped Cz wafers are also susceptible to LID [58].…”
Section: Decreasing the Boron Doping Concentrationmentioning
confidence: 99%
“…Though In and Ga are both viable alternatives to B‐dopants, the higher melting point of In (156 °C) can allow for improved doping uniformity in continuous Cz growth compared to Ga . Very few reports are available on the solar cell performance of In‐doped wafers and their LID response . Cho et al demonstrated 20.3% efficient PERC devices with no LID on Cz‐grown In‐doped wafers …”
Section: Introductionmentioning
confidence: 99%